Development of a Microcontroller-Based Portable Hemoglobin Meter Using Optical Sensing Techniques (International Journal of Food and Nutritional Sciences, 2023)
Hemoglobin is a protein pigment that is carried by oxygen throughout the body. The determination of iron deficiencies and anemia among the people is quickly helped by them to recover. Hence, the main purpose of designing the portable instrument is for the detection of hemoglobin to be accurate. Here, the microcontroller-based hemoglobin meter portable instrument with a color sensor is constructed using a RED LED of wavelength 620-660 nm and an OLED display. The samples for the detection of hemoglobin were collected and analysed during blood donation camps at Bordi, Gholwad and Umbergaon. Iron deficiencies among the people were quickly determined with less expense.